Explanation of Prohibitions on Agricultural Culture in the Structure, Social Function, and Trust of Kerinci Community - Rengki Afria; Neldi Harianto; Julisah Izar (Proceeding International Conference on Malay Identity, 2022)
Abstract: This study aims to describe Expressions of Agricultural Prohibitions In The Structure, Social Function, And Trust of The Kerinci Community. The research data is oral data with a qualitative descriptive method. Based on the results of this study, it can be concluded as follows. The level of trust of the people of Kerinci, in general, they believe in this prohibition. but the local people believe in this when they are farming or cultivating crops. Even though this prohibition sounds unreasonable or illogical, they still believe in the prohibition. The people's belief in the expression of this prohibition was made by the people of Kerinci, as a social function of old beliefs. Sometimes it's just a prohibition that scares a little, but there are still many lessons that can be drawn from the prohibition. Although not with knowledge based on theory, they succeeded in educating manners and behavior in society and used for themselves. Keywords: expression, agricultural prohibition, structure, social, function, trust